1946
DOI: 10.1085/jgp.29.6.413
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of the Yeast Yellow Protein

Abstract: The yellow protein crystallized by Kunitz and McDonald (7) from yeast has been examined for some of its properties. The crystalline preparations employed were kindly placed at my disposal by these authors. The yellow color of the preparation appears to be largely due to a flavin prosthetic group, though another yellowish prosthetic group also appears to be present. No enzymatic function for this protein preparation has as yet been found. EXPERIMENTALThe preparations of the yellow protein were received as a pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1950
1950
1960
1960

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Little is known about the protein-FAD linkage and the cause of its rupture by calcium chloride. Ball (1946), in an examination of the yellow flavoprotein prepared from yeast by Kunitz & McDonald (1946), found that it had an absorption spectrum in the visible region similar to that of xanthine oxidase except that the absorption at wavelengths greater than 500 mp. was -virtually absent.…”
Section: Prosthetic Group Of Xanthine Oxida8ementioning
confidence: 99%
“…Little is known about the protein-FAD linkage and the cause of its rupture by calcium chloride. Ball (1946), in an examination of the yellow flavoprotein prepared from yeast by Kunitz & McDonald (1946), found that it had an absorption spectrum in the visible region similar to that of xanthine oxidase except that the absorption at wavelengths greater than 500 mp. was -virtually absent.…”
Section: Prosthetic Group Of Xanthine Oxida8ementioning
confidence: 99%